Effect of different media on mycelium growth of Sclerotium rolfsii Sacc. invitro condition - Pandey, Prem; Gaire, Shankar P. (International Journal of Environment, Agriculture and Biotechnology, 2019)
An invitro experiment was conducted to study the effect of different culture media on mycelial growth of Sclerotium rolfsii Sacc. in Plant pathology Laboratory of Agriculture and Forestry University, Nepal. The pathogenic isolate of S. rolfsii was isolated from symptomatic tomato and maintained in PDA. Seven different culture media viz. Potato Dextrose Agar (PDA), Chickpea Dextrose Agar (ChDA), Bean Dextrose Agar (BDA), Carrot Dextrose Agar (CDA), Papaya Dextrose Agar (PpDA), Czapek Dox Agar (CzDA) and Sabouraud’s Dextrose Agar (SDA) were prepared and 5-mm diameter mycelial plugs from the margins of 3-days old S. rolfsiiculture was transfer in the middle of each media plate. The radial mycelial growth was measured at 2 days interval for 14 days. Chickpea Dextrose Agar (ChDA) had significantly higher mycelia growth, which was superior than Potato dextrose agar (PDA). Papaya fruit, carrot root, chickpea grain and bean grain can be the common cheap source of carbon in industrial development of culture media.